Temperature and Humidity Monitoring System - Anuar, Nur Amyra; Jalaludin, Nor Anija; Amirul Syafiq Sadun (Progress in Engineering Application and Technology, 2024)
This technical paper presents a comprehensive smart temperature and humidity monitoring system designed for diverse industries such as food manufacturing, agriculture, and construction. The system utilizes Internet of Things (IoT) technology to capture real-time temperature and humidity data in rooms, contributing to enhanced safety, equipment protection, and product quality control. The core components of the system include a nodeMCU microcontroller with ESP8266 Wi-Fi capabilities, enabling seamless data transmission to the Arduino IoT Cloud. The system employs the DHT11 temperature and humidity sensor to accurately detect environmental conditions. The Arduino IoT Cloud serves as the central platform, displaying captured data on a user-friendly dashboard. Additionally, the Arduino IoT Cloud Remote mobile application provides users with convenient access to monitor temperature and humidity readings on-the-go. To further enhance user awareness, the system integrates IFTTT (If This Then That) functionality, triggering notifications when environmental conditions deviate from predefined acceptable ranges. The prototype implementation involves a room scenario to validate the effectiveness of the temperature and humidity monitoring system. The results showcase the system's capability to safeguard workers, equipment, and products by preventing spoilage and mold growth. This paper contributes to the growing field of IoT applications in industrial settings, offering a scalable and adaptable solution for organizations requiring real-time environmental monitoring.